Perception of Veterinarians towards the Services Rendered by Animal Husbandry Assistants through Farmers Assurance Centers (Rythu Bharosa Kendras) - Priya Katti, Ranjani; Pulla, Sireesha; Bodapati, Subrahmanyeswari; Pothanaboina, Guru Vishnu; Lakshmi Bethapudi, Rajya; Deeptimahanti, Saisri (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Livestock farming plays a pivotal role in India’s agricultural sector, contributing significantly to the nation’s GDP. To enhance the quality  of services for livestock farmers, the state government of Andhra Pradesh has established Rythu Bharosa Kendras (RBKs) or what is  called Farmers Assurance Centers (FACs) at every Panchayat. The study focuses on veterinarians’ perception on the services provided  by Animal Husbandry Assistants (AHAs) through RBKs. Data was collected from 45 veterinarians from nine districts using structured  interview schedule and statistical analysis was employed to assess the perception of veterinarians. The findings revealed that significant  proportion of veterinarians had medium level of perception. The challenges faced by AHAs identified were inadequate knowledge  and skills and limited hands-on experience. It is concluded that the State Animal Husbandry Department should organize refresher  training programs for Animal Husbandry Assistants and Veterinarians should assess AHAs performance regularly and guide them in  providing better services.
Keywords: Animal Husbandry Assistants; Perception; Rythu Bharosa Kendras; Veterinarians